Greater Laxity in the Anterior Cruciate Ligament–Injured Knee Carries a Higher Risk of Postreconstruction Pivot Shift: Intraoperative Measurements With a Navigation System. Issue 12 (October 2018) - Yamamoto, Yuji; Tsuda, Eiichi; Maeda, Shugo; Naraoka, Takuya; Kimura, Yuka; Chiba, Daisuke; Ishibashi, Yasuyuki
Background: The presence of pivot shift after anterior cruciate ligament (ACL) reconstruction is correlated with worse clinical outcomes. An orthopaedic navigation system is a useful tool for quantifying laxity in the ACL-deficient knee. Purpose: To investigate the relationship between preoperative knee laxity measured by a navigation system and postoperative pivot shift (PPS) after ACL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: One hundred patients who underwent primary ACL reconstruction (62 hamstring tendon grafts, 38 patellar tendon grafts) were grouped according to the presence or absence of pivot shift at the 2-year follow-up, and the groups were compared retrospectively. Before surgery, knee laxity was assessed with a navigation system to quantify posterior tibial reduction (PTR) during pivot-shift tests and anterior tibial translation (ATT) during Lachman tests. PTR and ATT cutoff values were determined by receiver operator characteristic (ROC) analysis. Results: Preoperative PTR and ATT were significantly larger for patients with PPS (PPS-positive group) than those without (PPS-negative group). In the ROC analysis, the PTR had an area under the curve of 0.871 (95% CI, 0.763-0.979; P < .0001) for predicting a PPS; this was larger than that obtained for the ATT, which had an area under the curve of 0.825 (95% CI, 0.705-0.946; P = .001). Because the ROC curve of the ATT had 2 peaks, the ATT alone was not a suitable predictor for PPS. Based on the ROC curve, the optimal PTR cutoff value was 7 mm, with 88.9% sensitivity and 71.4% specificity for PPS (adjusted odds ratio = 19.7; 95% CI, 2.1-187.9; P = .009). Setting the cutoff value as a combination of the PTR (≧7 mm) and ATT (≧12 mm) improved the specificity (88.9% sensitivity and 84.6% specificity; adjusted odds ratio = 149.8; 95% CI, 5.9-3822.7; P = .002) over that with the PTR alone. Conclusion: ACL injuries in knees with a large PTR had a higher risk of PPS. When reconstructing the ACL in a knee with a high degree of laxity, surgeons may need to adopt strategies to prevent PPS.